Ideologized Politics – Change and Restructuring of Societal Consciousness: from National to Supra-National - Genov, Georgy (Research Papers, 2021)
The political activity at grass-roots level most often is perceived as verbal communications. Predominant part in the public and official discourse is due to ideology-burdened terms for „national (and alliance) interests”, „values (universal, democratic, European, euro-atlantic)” and „legitimacy”. For a third decade societal, group and individual consciousness is subjected to constant coordinated, institutionalized impact under the motto of „civilisational choice” aiming at a change of national identity (from Bulgarian into European, „European citizens”), substitution of traditional values for „European” (essentially neo-liberal). In fact a substitution of national interests with others, partially or entirely alien ones. The flow of the narrative interests-values-legitimacy marks the enlargement of subjective on behalf of the onjective.